2019
DOI: 10.5014/ajot.2019.031492
|View full text |Cite
|
Sign up to set email alerts
|

Complex Task Performance Assessment (CTPA) and Functional Cognition in People With Parkinson’s Disease

Abstract: OBJECTIVE. The objective of this study was to determine how Parkinson’s disease (PD) affects functional cognition as assessed by the Complex Task Performance Assessment (CTPA) and to examine the associations of CTPA performance with other indicators of executive function in people with PD. METHOD. Volunteers with PD without dementia (n = 20) and community control participants (n = 19) completed neuropsychological testing, patient-reported outcome measures, and the CTPA. RESULTS. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
5
6
0
Order By: Relevance
“…Reduced activity performance in the absence of neuropsychological test impairment has been observed in PD using a novel and complex work simulation activity. 46 The current study found performance limitations in more familiar and simpler tasks, which further supports the sensitivity of performance-based IADL assessment to early functional decline in PD. The longer time taken by participants with PD to complete the PASS is also consistent with studies that have used performance-based measures.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Reduced activity performance in the absence of neuropsychological test impairment has been observed in PD using a novel and complex work simulation activity. 46 The current study found performance limitations in more familiar and simpler tasks, which further supports the sensitivity of performance-based IADL assessment to early functional decline in PD. The longer time taken by participants with PD to complete the PASS is also consistent with studies that have used performance-based measures.…”
Section: Discussionsupporting
confidence: 81%
“…The longer time taken by participants with PD to complete the PASS is also consistent with studies that have used performance-based measures. 29 , 36 , 46 Of clinical relevance, this finding dovetails with qualitative work revealing that a major factor influencing daily function among people with PD is the increased time taken to perform daily activities. 47 Interestingly, although participants with PD perceived both physical and mental slowness in daily activities, 47 neither motor nor cognitive function were related to cognitive IADL performance time in this study.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It appears that the PD-NC group initiated the task quickly, without planning, and then used many strategies during task performance, which supported task accuracy but increased overall time and decreased efficiency. Prior studies using performance-based tests of cognitive instrumental activities of daily living have found that PD-NC participants take more time (Davis et al, 2019; Foster, 2014) and are less efficient despite good accuracy (Davis et al, 2019). PD-NC participants may have purposefully taken longer or gone slower during the task to maintain accuracy, but using more time at the beginning to assess the task and plan out the most appropriate approach may have been more effective in terms of overall efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, a 120 kVp scan is recommended. [13][14][15] Low-dose scanning includes various methods, such as reducing tube current, reducing tube voltage, coarse-pitch scanning, automatic tube voltage modulation, automatic tube current modulation, and the use of noise reduction filters and iterative reconstruction algorithms. Some studies 8 suggest that the dose of radiation has a linear relationship with the tube current and an exponential relationship with the tube voltage.…”
Section: Dovepressmentioning
confidence: 99%